Integrity Design for Networked Control Systems with Actuator Failures and Data Packet Dropouts. (21st November 2013) - Qi, Xiaomei; Gu, Jason
Abstract : The integrity design problem of fault tolerant control for networked control system (NCS) with actuator failures and data packet dropouts is investigated. The data packet dropouts in both sensor-controller (S-C) and controller-actuator (C-A) links are described by two switches, which can be modeled as a discrete event system with known rate. After introducing the matrix of actuator failure, the closed-loop NCS is developed, which can be viewed as asynchronous dynamical systems (ADSs). Then, the sufficiency of exponential stability for the NCS is obtained based on the theory of ADSs. The output feedback controllers that can guarantee system stability are also proposed. Finally, two numerical examples are given to demonstrate the validity of our proposed approach.